(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Amblyopia, commonly known as "lazy eye," is a childhood condition marked by reduced vision caused by developmental issues during early years. Detecting it early is crucial for successful treatment, which may involve interventions like eye patches, corrective glasses, or specialized therapies. Without timely intervention, it could lead to irreversible vision impairment. Anisometropia (different refractive errors in each eye) and strabismus (misalignment between the eyes) are primary causes, while conditions like retinopathy of prematurity, corneal trauma, and congenital cataracts can also contribute. Objectives: This study aimed to assess and measure the level of knowledge and awareness of amblyopia among medical students in Saudi Arabia. Methods: This was a cross-sectional study, in which data was collected at one point in time. A cross-sectional survey was carried out online starting on June 2023. Data was stored using Microsoft Office Excel and then was analyzed using descriptive statistics. Results: As regard the knowledge score about amblyopia, 58.5% of respondents fall into the category of poor knowledge. Additionally, only 25.6% of individuals demonstrated a good knowledge level. The fair knowledge segment, accounting for 15.9%. Regarding the awareness score, 23.3% of respondents exhibiting good awareness and 23.0% demonstrating fair awareness. Conversely, a striking 53.7% of respondents are categorized as having poor awareness. Regarding the relation between awareness of amblyopia and sociodemographic characteristics, there was a statistically significant relation to year of studying (p value=0.0001), age (p value=0.0001), personal history of eye disease (p value=0.002), and family history of eye disease (p value=0.003). It also shows statistically insignificant relation to gender, marital status, nationality, current GPA. Conclusion: this study highlighted a significant gap in knowledge and awareness of amblyopia among medical students in Saudi Arabia, with over half of the respondents categorizing as having poor awareness and knowledge of the condition. Despite the pivotal role that medical professionals play in the early detection and intervention of amblyopia, the low levels of understanding regarding its definitions, risk factors, and optimal treatment timelines underscore the need for enhanced educational initiatives. The findings align with previous research indicating that awareness of amblyopia is notably insufficient, even within medical circles.